2000
DOI: 10.1074/jbc.275.13.9425
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil-specific Regulation of gp91 Gene Expression by Transcription Factors GATA-1 and GATA-2

Abstract: The glycoprotein gp91phox is an essential component of the phagocyte NADPH oxidase and is expressed in eosinophils, neutrophils, monocytes, and B-lymphocytes. We previously suggested an eosinophil-specific mechanism of gp91 phox gene expression. To elucidate the mechanism, we performed functional assays on deletion mutants of the gp91 phox promoter in various types of gp91 phox -expressing cells. A 10-base pair (bp) region from bp ؊105 to ؊96 of the promoter activated transcription of the gene in eosinophilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 42 publications
0
28
1
2
Order By: Relevance
“…We have shown that eosinophil-committed promyelocytic cell lines express GATA-1-3 mRNA in an inducible fashion, and peripheral blood eosinophils of mixed developmental maturity isolated from patients with the hypereosinophilic syndrome also express GATA-1 mRNA (21). Studies in the avian system using myb-ets-transformed myeloid progenitors have suggested that an intermediate level of GATA-1 expression in the context of C/EBP␤ and PU.1 is critical for eosinophil lineage-specific gene expression and differentiation (1,2,7,12,22). As well, GATA-1 expression is slowly down-regulated during eosinophilopoiesis in the avian system (3,7).…”
Section: Family (C/ebp␣mentioning
confidence: 99%
“…We have shown that eosinophil-committed promyelocytic cell lines express GATA-1-3 mRNA in an inducible fashion, and peripheral blood eosinophils of mixed developmental maturity isolated from patients with the hypereosinophilic syndrome also express GATA-1 mRNA (21). Studies in the avian system using myb-ets-transformed myeloid progenitors have suggested that an intermediate level of GATA-1 expression in the context of C/EBP␤ and PU.1 is critical for eosinophil lineage-specific gene expression and differentiation (1,2,7,12,22). As well, GATA-1 expression is slowly down-regulated during eosinophilopoiesis in the avian system (3,7).…”
Section: Family (C/ebp␣mentioning
confidence: 99%
“…Constructs pϪ267/Luc, pϪ115/Luc, pϪ95/Luc, and pϪ84/Luc were prepared using the PCR method using pGV-267/Luc which had the fragment of the gene extending from its initiation codon to upstream bp Ϫ267 as the template as described previously in detail (21). A mutant of GAS (pϪ115GASm/Luc) with a two-point mutation (TC to AG) from the bp Ϫ103 to Ϫ102 and a mutant of ISRE (pϪ115IRFm/Luc) with a fivepoint mutation (AGGG to TCCC) from bp Ϫ87 to Ϫ84 were prepared from pϪ115/Luc by PCR using a mutated primer.…”
Section: Methodsmentioning
confidence: 99%
“…HAF-1 is a multiprotein complex, and its components are still not defined, but PU.1, IRF-1, ICSBP, and Elf-1 are picked out as candidates (19,20). GATA-1, GATA-2, and GATA-3 regulate transcription of the gp91 phox gene in eosinophilic cells (21,22). IFN-␥ is a cytokine that plays an important role in both innate and adaptive immunities (23).…”
Section: Several Transcription Factors Regulate Gp91mentioning
confidence: 99%
“…However, it is not clear whether the double-GATA site is essential for the transcriptional activation of eosinophil-specific genes. Charcot-Leyden crystal protein (27) and gp91phox (40) are encoded by eosinophil-specific genes that contain a single-GATA site in their promoters, and mutation of these GATA sites significantly suppresses transcriptional activity. In addition, although the MBP P2 promoter contains a double-GATA site, mutation of one of the two GATA subsites is sufficient to inhibit transcriptional activity (26).…”
Section: Discussionmentioning
confidence: 99%